OPORTUNIDADES DE NEGOCIOS: APEC, COREA DEL SUR Y PERÚ - Mauricio Pachas, Pablo (2008)
The present article treats on the foreign trade of the Korean economy and its participation in the Asia Pacífic Economic Cooperation (APEC) Forum, the Peruvian exports and the Korean importings, as well as the main countries of destiny and origin, and main products marketed by both economies. The opportunities of commerce with the market of South Korea they are emphasized and their relation with the current exportable offering of our country, inside the framework of the Forum APEC.